The burden of vaccine hesitancy for routine immunization in Yaounde-Cameroon: A cross-sectional study - Martin Ndinakie Yakum; Atanga D. Funwie; Atem Bethel Ajong; Marcellin Tsafack; Linda Evans Eba Ze; Zahir Shah (Public Library of Science (PLoS), 2022)
Immunization is the most cost-effective health intervention in the world yet, vaccination uptake is still low with less than 50% of children aged 12-23 months fully vaccinated in Cameroon by 2018. The objective of this study was to estimate the burden of vaccine hesitancy associated with routine vaccines in Yaounde-Cameroon. A two-stage cross-sectional cluster survey was conducted in Yaoundé in November 2021, targeting parents/guardians of children 0-59 months. Clusters were selected with probability proportionate to size (PPS) and household's selection done using a restricted sampling method. Data collection was done using an interviewer-administered questionnaire, "Core Closed Questions" and "Likert Scale Questions" proposed by the WHO Vaccine Hesitancy Technical Working Group in 2014. Vaccine hesitancy was analyzed as proportions of parent's/guardian's self-reported vaccine refusal or delay in vaccination with 95% confidence interval. This was stratified by household wealth level and tested using Chi-Square test to appreciate the effect of household wealth on vaccine hesitancy. A total of 529 participants were enrolled out of 708 visited, giving a non-response rate of 25%. In total, vaccine hesitancy was reported in 137(25.90[22.35-29.80] %), and oral polio vaccine(OPV) was the most affected vaccine with hesitancy of 10%. Vaccine hesitancy prevalence did not vary significantly across different households' wealth levels (p-value = 0.3786). However, in wealthy households' refusal of vaccines (14%) was less than in poorer households (20%). Lack of trust was reported as the leading cause of vaccine refusal (43%). Vaccine hesitancy prevalence in Yaounde is high and oral polio vaccine(OPV) was the most affected vaccine. The level of weath does not affect vaccine hesitancy and lack of trust was the leading cause of vaccine hesitancy related to routine immunization in Yaounde-Cameroon. We, recommend that the burden of vaccine hesitancy should be assessed at national scale and root causes investigated.